Fecal immunochemical tests detect screening participants with multiple advanced adenomas better than T1 colorectal cancers - Gies, Anton; Niedermaier, Tobias; Gruner, Laura Fiona; Heisser, Thomas; Schrotz-King, Petra; Brenner, Hermann (Cancers, 2021)
Background: Fecal immunochemical tests (FITs) are widely used for colorectal cancer (CRC) screening. The detection of early-stage cancer and advanced adenoma (AA), the most important premalignant lesion, is highly relevant to reducing CRC-related deaths. We aimed to assess sensitivity for the detection of CRC and AA stratified by tumor stage; number; size; histology of AA; and by location, age, sex, and body mass index (BMI). Methods: Participants of screening colonoscopy (n = 2043) and newly diagnosed CRC patients (n = 184) provided a stool sample before bowel preparation or CRC surgery. Fecal hemoglobin concentration was determined in parallel by nine different quantitative FITs among 94 CRC patients, 200 AA cases, and 300 participants free of advanced neoplasm. Sensitivities were calculated at original cutoffs and at adjusted cutoffs, yielding 93% specificity among all FITs. Results: At adjusted cutoffs, UICC stage I cancers yielded consistently lower sensitivities (range: 62-68%) compared to stage II-IV cancers (range: 73-89%). An even stronger gradient was observed according to T status, with substantially lower sensitivities for T1 (range: 39-57%) than for T2-T4 cancers (range: 71-100%). Sensitivities for the detection of participants with multiple AAs ranged from 55% to 64% and were by up to 25% points higher than sensitivities for T1 cancers. Conclusions: FITs detect stage I cancers and especially T1 cancers at substantially lower sensitivities than more advanced cancer stages. Participants with multiple AAs were detected with slightly lower sensitivities than stage I cancers and with even higher sensitivities than T1 cancers. Further research should focus on improving the detection of early-stage cancers.
Gesehen am 31.03.2021